Bullying from a Legal Perspective - Suharti, Eni; Hamdani, Hamdani; Zatira, Dhea; Mutiara, Upik; Ahmad, Ahmad; Rohaya, Nizla; Warsito, Warsito (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to increase knowledge about the legal consequences for bullying perpetrators and to raise awareness among students and teachers about bullying in schools. The outreach was conducted in person at SMAN 7 in South Tangerang City using a survey method, involving both students and teachers. Information was delivered directly through presentations and discussions, and data was collected on students' initial knowledge of the legal implications of bullying before and after the outreach. The results showed that most students were unaware that bullying by minors could lead to criminal charges, although the legal treatment differs from that of adult criminal cases. These findings highlight the importance of legal education in schools to enhance understanding of the legal consequences of bullying, and the need for ongoing education to ensure that everyone in the school environment is adequately aware of the legal implications of bullying, thereby creating a safe and conducive learning environment.